Hubungan Antara Aktivitas Fisik Dan Kualitas Tidur Mahasiswa Fakultas Kedokteran Universitas Tarumanagara - Shabrina Maharani, Syifa; Halim, Susilodinata (Journals of Ners Community, 2023)
The World Health Organization (WHO) defines physical activity as every time a person's skeletal muscles move, whether it be during leisure, employment, or travel, and uses energy. This includes both daytime and nighttime activities or one day activity. In order to recharge our bodies, sleep is a must. After a day of physical exertion or job, the body will send a signal to rest, usually in the form of fatigue. Methodology uses observational analysis research and cross-sectional techniques (cross-tabulations) which were conducted in February and March 2023 at Tarumanagara University. Samples will be collected using a simple random sampling method called probability sampling. Information from respondents will be displayed in tabular format (Frequency and Percentage). The data from the research will be displayed in a 2x2 table and evaluated using chi-square statistic. Results of this study collected data from 198 respondents, 54 of whom reported doing mild physical activity (27,3%), 144 of whom reported doing moderate to severe physical activity (72,7%), and the quality of sleep collected by the respondents was the quantity sleep. There were 93 respondents with good sleep quality (47%) and 105 respondents with poor sleep quality (53%). Thus, 72,7% of the sample is in the moderate to severe physical activity category, while 53% have poor sleep quality. With p-value of 0,000 or p<0,05. The conclusion is that students of Faculty of Medicine, University of Tarumanagara have a strong (significant) connection between the intensity of physical activity and quality of sleep that they experience.